Workshop pengukuran nilai kalori harian atlet berdasarkan jenis olahraga - Arimbi Arimbi; Sudiadharma Sudiadharma; Poppy Elisano Arfanda (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The body's need for nutrition is absolute, nutrient needed to maintain cell life in the body, both at rest and during exercise. An athlete must have good stamina in supporting his achievement improvement. Good stamina for an athlete can only be obtained if you consume nutrients that suit your needs both during training and when competing. All the nutrients that the body needs are found in the food we eat everyday. The need for absolute nutrients for the body to carry out its normal functions. The energy is obtained from food eaten by a swimming athlete every day. Proper food will be able to produce good physical condition, because the food will provide energy according to the needs of his body in his daily life.